Evidence for Deeper Hydrocarbon Exploration: New Insight from the Hydrocarbon Plays in the North Celtic Sea Basin - God'spower I. Onyenanu (Journal of ICT, Design, Engineering and Technological Science, 2017)
This study adds to previously published works, which were based on 1D modelling, by generating 2D models using PetroModTM software. Seismic data have been used to reconstruct the regional structural framework, while the integrated wireline logs and geochemical data provided lithological, porosity, and palaeothermal information. The palaeothermal values and available vitrinite reflectance data have been used to calibrate the models to present-day heat flow of 52mW/m2. Results from this study show that hydrocarbon maturation, generation, and migration were affected by the Triassic and Late Jurassic rifting activities, resulting in a complex charge history and trap modification through time. The Late Jurassic source rocks (PurbecK) attained peak maturation for oil in the late Cretaceous, while the Early Jurassic Source rocks (Liassic and Toarcian) entered the gas window in the Early Cretaceous. Analysis of the petroleum systems for deeper hydrocarbon prospecting suggests that two expulsion phases of hydrocarbons occurred in the Late Jurassic and Early Cretaceous, respectively. This result suggests that there is potential for the charge of suitable reservoir facies at depth if the reservoir quality can be preserved. Hydrocarbon preservation risk is low in anticlinal structures, but there is a high risk of hydrocarbon remigration along modified fault planes in fault-dependent structures. The study demonstrates how basin geometry has changed through time due to multiple tectonic events, leading to modification of older traps.